Pengaruh Motivasi Belajar Siswa di Masa Pandemi di SDN 1 Natai Sedawak - Silvia Muna Rosida; Henry Aditia Rigianti (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2022)
This research was conducted with the aim of finding and digging up information about online learning during the pandemic, because many students do not have mobile phones. in this study with the interview method and also with documentation. Interviews were conducted to gain insight into online learning for elementary school students. Documentation is done to find out how the actual conditions of online learning are, because there are no facilities from the school. The results of this study indicate that students have difficulty participating in online learning because of the absence of technological facilities in schools.